2018
DOI: 10.1016/j.polymertesting.2018.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of material removal when cutting natural fiber reinforced thermoplastic composites

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. This is an author-deposited version published in: https://sam.ensam.eu Handle ID A B S T R A C TThis paper aims to study the machinability of natural fiber reinforced thermoplastic composites by investigating the mechanics of chip formation and the multiscale cut surface's quality induced by the orthogonal cutting process. Unidirectional flax fibers reinforced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 46 publications
4
30
1
Order By: Relevance
“…In this paper, the considered NFRP sandwich part is elaborated with a thermoset matrix (Acrodur resin). However, This cutting behavior of flax fibers is similar to that demonstrated in the previous author's works [30,31,33] where the same tribo-physical phenomena that occur on flax fibers during cutting process are founded via the current industrial application (fibers deformation, interfaces cracking, uncut fiber extremities, …) regardless of the matrix nature (Acrodur or polypropylene). Thus, it can be concluded that the behavior of the plant fibers during the cutting is independent of the matrix choice (thermoset or thermoplastic) used for manufacturing the NFRP composites.…”
Section: Cutting-induced Surface Finishsupporting
confidence: 83%
See 2 more Smart Citations
“…In this paper, the considered NFRP sandwich part is elaborated with a thermoset matrix (Acrodur resin). However, This cutting behavior of flax fibers is similar to that demonstrated in the previous author's works [30,31,33] where the same tribo-physical phenomena that occur on flax fibers during cutting process are founded via the current industrial application (fibers deformation, interfaces cracking, uncut fiber extremities, …) regardless of the matrix nature (Acrodur or polypropylene). Thus, it can be concluded that the behavior of the plant fibers during the cutting is independent of the matrix choice (thermoset or thermoplastic) used for manufacturing the NFRP composites.…”
Section: Cutting-induced Surface Finishsupporting
confidence: 83%
“…These pertinent scales correspond to the size of the fibrous structure regardless of the reinforcement structure type. This founding has been also confirmed by an orthogonal cutting investigation on UD flax fibers reinforced PP matrix [33] which proves that the multiscale behavior of NFRP composites is independent of the process type. Indeed, the intimate relationship between the relevant scales and the fibrous structure size has been previously confirmed by nanoindentation and scratch test measurements where the authors show the scale effect on the tribo-mechanical performances of flax fibers [46,47].…”
Section: (C)supporting
confidence: 67%
See 1 more Smart Citation
“…Moreover, the machinability analysis of NFRP composites requires the consideration of an appropriate analysis scale. The pertinent analysis scale for NFRP machining is related to the natural fibrous reinforcement size [17][18][19][20][21] because the tribo-mechanical response of natural fibers inside composite materials is strongly dependent on the contact scale [22][23][24]. However, the machining processes are not purely based on tribo-mechanical phenomena since the machining operations induce significant temperature increase due to the high deformation rate and high tool/material friction [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Mejri et al [9] prepared birch fiber and high density polyethylene composite for replacing nylon which is used in spur gear manufacturing in industries. Chegdani et al [10] studied on machinability of natural fiber-reinforced composite material by investigating the mechanics of chip formation and the multiscale cut surface by orthogonal cutting experiment. Vignesh G et al [11] prepared hybrid composite materials with kenaf, human hair as reinforcements, and epoxy resin as matrix for investigating its mechanical properties such tensile strength, flexural strength, and impact strength.…”
Section: Introductionmentioning
confidence: 99%